"Alexa, can we design gamification without a screen?" - Implementing cooperative and competitive audio-gamification for intelligent virtual assistants. (October 2022) - Bräuer, Paula; Mazarakis, Athanasios
Abstract: Intelligent virtual assistants (IVAs) like Amazon Alexa or Google Assistant have become increasingly popular in recent years, and research into the topic is growing accordingly. A major challenge in designing IVA applications is making them appealing. Gamification as a concept might help to boost motivation when using IVAs. Visual representation of progress and feedback is an essential component of gamification. When using IVAs, however, visual information is generally not available. To this end, this article reports the results of a lab experiment with 81 subjects describing how gamification, utilized entirely by audio, can assist subjects to work faster and improve motivation. Game design elements such as points and levels are integrated within an Alexa Skill via audio output to motivate subjects to complete household tasks. The results show a substantial effect on the subjects. Both their attitude and the processing time of the given tasks were positively influenced by the audio-gamification. The outcomes indicate that audio-gamification has a huge potential in the field of voice assistants. Differences in experimental conditions were also considered, but no statistical significance was found between the cooperative and competitive groups. Finally, we discuss how these insights affect IVA design principles and future research questions. Highlights: Motivational effects of gamification are analyzed in the context of IVAs. A between-subjects experiment with cooperative and competitive groups was executed. Results show gamification can raise motivation and performance for screenless IVAs. The cooperative and competitive groups' performance and motivation did not differ. Results suggest gamification does not require a visual component to be successful.